Uniformity simulation of multiple-beam irradiation of a spherical laser target with the inclusion of radiation absorption and refraction. (February 2019) - Demchenko, N.N.; Gus'kov, S.Yu.; Zmitrenko, N.V.; Rozanov, V.B.; Stepanov, R.V.
Abstract: We consider the physicomathematical model for the simulation of the angular laser flux distribution in a spherical target with the inclusion of radiation refraction in the corona. The irradiation uniformity is simulated using the target irradiation scheme on a megajoule multiple-beam laser facility. Calculations are made of the time-dependent angular distribution of absorbed flux and of the angular distribution of the time-integrated characteristic – the absorbed energy with allowance for the temporal shape of laser pulses – as well as of the time dependence of absorption efficiency. Different versions of target irradiation are considered. Under conventional irradiation it is assumed that the axes of all laser beams of equal energy pass through the target centre and the irradiation nonuniformity is due to its geometry only. Also examined are three unconventional irradiation versions: when there is a small spread of beam energies, when the target is displaced from the common beam pointing centre, and when the beam axes have small random deviations from the target centre. It is shown that the nonuniformity of the angular distribution of absorbed flux is greatest when the target is displaced from the beam pointing centre.